The effect of ultrasonic vibrations with superimposed low-frequency modulation on the mechanical, tribological properties and structure of a multicomponent polymer composite - D. A. Negrov; V. Yu. Putintsev; A. I. Glotov; D. A. Veber (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
One of the tasks of polymer materials science is to study the possibilities of improving the complex of elastic-strength characteristics and tribological properties of polymer composite materials by improving the manufacturing technology. In this paper, the influence of ultrasonic vibrations with a frequency of 17 kHz with a low-frequency vibration with a frequency of 100 Hz during synthesis on the properties and structure of a multicomponent polymer composite material of the KVN-3 trademark is considered. The result of the research, it is found that the influence of the technological mode of pressing, consisting in the combined effect of ultrasonic vibrations with frequency and low-frequency vibration during the synthesis of KVN-3, makes it possible to increase the complex of elastic-mechanical characteristics: tensile strength by 3 %, elongation by 6 %, modulus of elasticity by 10 %, hardness by 2 %, compared to the industrial manufacturing method, as well as to reduce the intensity of mass wear by 68 % and the coefficient of friction by 3 %. The structure of polymer composite materials after different technological pressing modes is examined. The fibrillar structure of the polymer matrix after the technological regime with the influence of ultrasonic vibrations and low-frequency modulation becomes finer and more uniform.